1998
DOI: 10.1021/bi9815389
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Properties of ba3 Oxidase from Thermus thermophilus:  Effect of Temperature

Abstract: The kinetic properties of the ba3 oxidase from Thermus thermophilus were investigated by stopped-flow spectroscopy in the temperature range of 5-70 degrees C. Peculiar behavior in the reaction with physiological substrates and classical ligands (CO and CN-) was observed. In the O2 reaction, the decay of the F intermediate is significantly slower (k' = 100 s-1 at 5 degrees C) than in the mitochondrial enzyme, with an activation energy E of 10.1 +/- 0.9 kcal mol-1. The cyanide-inhibited ba3 oxidizes cyt c522 qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
108
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 41 publications
6
108
1
Order By: Relevance
“…This feature is not observed in the NO-bound form, and, by analysis in comparison with the CO second-derivative spectra (21), we estimate that NObinding occurs for more than 97%. This finding is consistent with the observation that NO complements ligand binding to heme a 3 in the fraction of CO-equilibrated enzymes that does not form the heme a 3 -CO complex (24).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This feature is not observed in the NO-bound form, and, by analysis in comparison with the CO second-derivative spectra (21), we estimate that NObinding occurs for more than 97%. This finding is consistent with the observation that NO complements ligand binding to heme a 3 in the fraction of CO-equilibrated enzymes that does not form the heme a 3 -CO complex (24).…”
Section: Resultssupporting
confidence: 91%
“…In particular, binding of CO to this enzyme leads to formation of only 70% of the heme a 3 -CO complex (21,24), with the remaining 30% forming a CuB-CO complex (25). To estimate the extent of NO binding to heme a 3 , the inset of Figure 1B shows the second derivative of the Soret spectra of the unligated and NO-bound forms.…”
Section: Resultsmentioning
confidence: 99%
“…ence on ionic strength, but it should be kept in mind that our experimental approach, in contrast to a turnover assay (19), only follows the initial steps of encounter and ET between the two proteins. Thus the fast kinetics observed here do not depend on a sluggish off-rate and therefore are only moderately affected by ionic strength (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into consideration that the stability of electrostatic interactions is lower at higher temperatures, hydrophobic interactions become more favorable. Kinetic studies have shown that the turnover activity of cytochrome c 552 with ba 3 oxidase becomes faster as ionic strength is decreased (19). On the contrary, P. denitrificans aa 3 cytochrome-c oxidase shows very low turnover rates under low ionic strength conditions, most likely because of the formation of a high affinity electrostatic complex (15).…”
mentioning
confidence: 99%
“…They often exhibit significantly different structural features, like for example the cyt c552 from the thermophilic bacterium Thermus thermophilus, which possesses only uncharged residues around the exposed heme edge [25][26][27]. Mainly hydrophobic interactions are thus believed to take place between cyt c552 and the corresponding cyt c oxidases in T. thermophilus [25,28,29]. Bacteria also use diheme proteins to transfer electrons between the respiratory enzyme complexes, such as the cyt c4, which are native electron donors of C family (cbb3) oxidases [30,31].…”
Section: Introductionmentioning
confidence: 99%